SOCIALIZATION OF PRODUCT BRANDING AS AN EFFORT TO INCREASE ENTREPRENEURIAL INTEREST AMONG HOUSEWIVES OF NGINDEN JANGKUNGAN VILLAGE - Harya, Gyska Indah; Rusyda, Ahmad Naufal; Pramesti, Anselma Abistha; Puspitasari, Dian; Gifani, Jenny Amelia (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Product branding provides various potentials in increasing sales value so that it can attract consumers, product branding can be developed in MSMEs which play an important role in national economic growth. MSMEs are also considered as one of the solutions for people who do not have jobs or do not want to work in a company. One of them is in the Nginden Jangkungan sub-district which still does not have an adequate understanding of product branding, so efforts are needed to increase awareness and understanding, one of which is through socialization. With the socialization related to product branding, it is expected to increase product competitiveness, attract consumer attention and increase income.